PROTOCOLO DE ACOLHIMENTO DE SERVIÇO EM UNIDADE OBSTÉTRICA: FERRAMENTA PARA TOMADA DE DECISÃO - Segalin, Vânia Terezinha Rigo (2020)
Introduction: Around the 20th century, a productive model emerged, based on the flexibility of the labor market, which stimulated an increasingly qualified, proactive and entrepreneurial professional standard. The nursing area raises the need for professionals who envision differentiated, qualified care, with a view to best practices and management of work processes, to exercise their autonomy, leadership and decision making. Specifically, in Obstetric Units, the nurse manages the care to facilitate the nursing care offered to the parturient, the baby and the family. In this way, it uses the service protocols strategy to support care and management practices, minimizing weaknesses in work processes. Objectives: To know autonomy and governance strategies for nurses'decision making in an obstetric unit and to create a service reception protocol as a strategy for autonomy and governance in an obstetric unit. Method: Descriptive, applied and qualitative study. Data collection was carried out in December 2019, after institutional procedures and approval by the Ethics and Research Committee. For data collection, structured interviews were conducted using a three-dimensional form. The dimensions that covered the instrument were: Dimension I - Sociodemographic profile of the professionals; Dimension II - Professional and Dimension III - Autonomy. The research results supported the construction of a service protocol for the obstetric unit, which followed the steps recommended by the National Health Surveillance Agency and scientific evidence available in the literature. Results: To meet the first objective, a qualitative field study was carried out with nine nurses from an obstetric unit in a public hospital in southern Brazil. The data obtained showed that the participants were between 41 and 50 years old and had a professional training period of 12 to 20 years, the majority being specialists, with time in the hospital from five to 11 years and the time in the obstetric unit varying from eight months to six years. In the second and third dimensions, nurses emphasized autonomy and governance strategies and outlined the practices of care management and professional experience as facilitators for this management. Regarding the second objective, the experience of creating a service reception protocol for the obstetric unit was reported, which will serve as a tool to support the autonomy and governance of nurses, as well as a model of guidance for a succinct and systematic analysis of situations that threaten the woman's life and how to organize the different demands of users, providing more appropriate responses to each case. Generated product and applicability: After conducting the research with the nurses of the obstetric unit of high risk and habitual risk, the issues inherent to the construction of a protocol for the reception service to women, were considered as trigger subsidies for this construction. Thus, this protocol was created in line with the institution's organizational and operational structure. Its applicability and relevance are due to the fact that the institution does not yet have such technology and is configured as a high risk unit, promoting the need and importance of this product. In addition, it was agreed and requested by the managers of the hospital, as it is an element recommended by the Ministry of Health.